Effects of Age-related Differences in Empathy on Social Economic Decision-Making - Beadle, Janelle N. (2012)
BACKGROUND: The ways in which aging affects social economic decision-making is a central issue in the psychology of aging. To examine age-related differences in social economic decision-making as a function of empathy, 80 healthy volunteers participated in the Repeated Fixed Opponent Ultimatum Game (UG-R). Previous economic decision making research has shown that in younger adults empathy is associated with prosocial behavior. The effects of empathy on older adult social economic decision-making are not well understood. METHODS: On each of 20 consecutive trials in the UG-R, one player (“Proposer”) splits ten dollars with another player (“Responder”) who chooses either to accept (whereby both receive the proposed division) or reject (whereby neither receives anything). Trait cognitive and emotional empathy were measured using the Interpersonal Reactivity Index. RESULTS: UG-R data were examined as a function of age and cognitive empathy. For unfair offers (i.e., offers less than $5), older Responders with high cognitive empathy showed less prosocial behavior and obtained greater payoffs than younger Responders with high cognitive empathy. CONCLUSIONS: High levels of cognitive empathy may differentially affect economic decision making behavior in younger and older adults. For older adults, high cognitive empathy may be involved in obtaining high financial payoffs while for younger adults it may instead facilitate social relationships.